Acceptable IS Use: Conceptualization and measurement. (February 2016) - Goel, Lakshmi; Hart, Dana; Junglas, Iris; Ives, Blake
Abstract: We investigate the use of systems in situations that are subjective. In these situations, usage behaviors are often guided by applied ethical perceptions, rather than absolutes of what can or should be done. Using a scenario-based randomized survey, we developed and tested the concept of "Acceptable IS Use" to measure individual perceptions of use in such situations. Our contributions are a) the conceptualization of Acceptable IS Use grounded in applied ethics theories; b) measurement of the construct through a scale with demonstrated validity and reliability, and c) showing that perceptions of Acceptable IS Use can be influenced. Highlights: We conceptualize Acceptable IS Use grounded in applied ethics theories. We measure the construct through a scale with demonstrated validity and reliability. We show that perceptions of Acceptable IS Use can be influenced. We suggest avenues for future research that incorporate the concept of Acceptable IS Use.